Political Violence and Secondary School Education in Nigeria: A Case Study of Bette-Bendi People of Cross River State - Osakpa, David U. (Mediterranean Journal of Social Sciences, 2012)
The main objective of conducting this study was to examine and analyze, in the context of Bette-Bendipeople of Cross River State, Nigeria, the relationship between political violence and secondary schooleducation and test for causality between them. Bette-Bendi people, who are in the volatile Niger Deltaregion, were used as case study. Three research questions and three null hypotheses were formulated toguide the research. Data gathered were analyzed with the x2, v-statistic and factor analysis involving fifteenvariables. All three null hypotheses were rejected in favour of their alternatives. The main finding confirmeda strong relationship between political violence and secondary school education. The study concluded thatthe Nigerian government should set up a Committee of Experts to develop a Survivalist Curriculum in linewith the work of Academic Associates Peace Works in Taraba and Delta States as the most ideal forsecondary school education in Bette-Bendi and all politically violent and unstable areas for a permanentresolution of crises and behaviour control in those areas throughout the country.